1995
DOI: 10.1084/jem.182.2.345
|View full text |Cite
|
Sign up to set email alerts
|

The alpha 4 integrin chain is a ligand for alpha 4 beta 7 and alpha 4 beta 1.

Abstract: SummaryThe heterodimeric ol4 integrins c~4~7 lymphocyte Peyer's patch adhesion molecule ([LPAM]-I) and ol431 (very late antigen-4) are cell surface adhesion molecules involved in lymphocyte trafficking and lymphocyte-cell and matrix interactions. Known cellular ligands include vascular cell adhesion molecule (VCAM)-I, which binds to ~431 and ol437, and the mucosal addressin cell adhesion molecule (MAdCAM)-I, which binds to ol437. Here we show that the o~4 chain of these integrins can itself serve as a ligand. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 57 publications
3
39
0
1
Order By: Relevance
“…In addition to fibronectin, the matrix protein osteopontin can interact with the ␣ 4 integrin (47). In another study the ␣ 4 integrin could bind homotypically to the ␣ 4 integrin chain via a conserved LDV motif (48). Another possibility is that MAdCAM-1 could be the ligand for ␣ 4 integrin if the integrin is in a high affinity state (as appeared to be the case for neutrophils in our in vitro studies).…”
Section: Discussionmentioning
confidence: 97%
“…In addition to fibronectin, the matrix protein osteopontin can interact with the ␣ 4 integrin (47). In another study the ␣ 4 integrin could bind homotypically to the ␣ 4 integrin chain via a conserved LDV motif (48). Another possibility is that MAdCAM-1 could be the ligand for ␣ 4 integrin if the integrin is in a high affinity state (as appeared to be the case for neutrophils in our in vitro studies).…”
Section: Discussionmentioning
confidence: 97%
“…Integrin ␣4␤7 (LPAM-1) expressed in a subset of effector T cells or ␥␦T cells in the intestine 31,32 can mediate cell migration as a receptor for MAdCAM-1 and VCAM-1. [33][34][35] Therefore, the expression of integrin ␤7 in Nanog T cells BLOOD, 1 JULY 2007 ⅐ VOLUME 110, NUMBER 1 For personal use only. on May 12, 2018.…”
Section: Discussionmentioning
confidence: 99%
“…Potential mechanisms include increased costimulatory signals and/or overstabilization of normally low-affinity TCR-Ia interactions. Recently it was shown that CD49d itself can also act as a cellular ligand for both ␣ 4 ␤ 1 and ␣ 4 ␤ 7 , with functional consequences (44). Increased CD49d expression may therefore also provide an increased costimulatory signal to the adjacent CD49d transfectant cells.…”
Section: Discussionmentioning
confidence: 99%